Effects of Microstructure of Aluminum Substrate on Ordered Nanopore Arrays in Anodic Alumina. Issue 7 (July 2015) - Chi, Choong-Soo; Lee, Jong-Ho; Kim, Insoo; Oh, Han-Jun
Abstract : The effects of microstructure of aluminum substrate on regular nanopore arrangement in anodic alumina layer were investigated. The dissimilar microstructure and texture on aluminum sheets were prepared by various cold rollings and heat treatments, and anodic alumina nanoporous layers were fabricated by two step anodizing method at 40 V in oxalic acid solution. For the aluminum sheets with similar surface texture and annealing condition except purity, the regularity of the nanopore arrangement on the anodic alumina layer increased with purity of aluminum substrate. The difference of surface texture on Al sheets is not critical parameter for formation of ordered nanopore array compared with purity and heat treatment of substrate aluminum. The investigation suggested that the purity and reasonable annealing temperature of aluminum substrate are very important process to obtain the highly-ordered nanopore array on anodic alumina layer.